PENGEMBANGAN CRACKERS SUMBER PROTEIN DAN MINERAL DENGAN PENAMBAHAN TEPUNG DAUN KELOR (Moringa oleifera) DAN TEPUNG BADAN-KEPALA IKAN LELE DUMBO (Clarias gariepinus) - Ai kustiani; Clara Meliyanti Kusharto; Evy Damayanthi (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2017)
Kelor is one of the vegetables with high nutrients contents but haven’t been widely utilized. Adding kelor leaves flour to the crackers made with catfish flour to increase protein and minerals is one way to maximize the potential of its nutrient content. This research purposed to develop the formulation of crackers by adding kelor leaves flour and catfish dumbo flour as a food source of protein and minerals. Kelor leaves flour obtained from this research contains protein, calcium, iron, and zinc respectively for 23.25%, 640.5 mg/100g, 30.6 mg/100g, and 6.65 mg/100g. The best formula chosen from organoleptic was is crackers with the addition 10% catfish dumbo flour and 2.5 g kelor leaves flour. The crackers contain 11.50% protein, 30.73 mg/100g calcium, 8.56 mg/100g iron, and 609.70 mg/100g zinc respectively. Selected crackers contain more than 20% protein and more than 15% of iron and zinc standart for 2-5 years old children group based on nutrition label reference (ALG, for Indonesian), so it can be claimed as a food source of protein, iron and zinc.